2000
DOI: 10.1029/2000jb900183
|View full text |Cite
|
Sign up to set email alerts
|

The stability and P–V–T equation of state of CaSiO3 perovskite in the Earth's lower mantle

Abstract: Abstract.Energy dispersive X-ray diffraction measurements for polycrystalline CaSiO3 perovskite were carried out at in situ transition zone and lower mantle P-T conditions (P=18-96 GPa, T=1238-2419 K) using the diamond anvil cell and double-sided laser heating at the GeoSoilEnviro Consortium for Advanced Radiation Sources (GSECARS) sector of the Advanced Photon Source. An analysis of the temperature error sources in laser heating reveals that the axial and radial thermal gradients are the greatest error source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 47 publications
9
62
3
Order By: Relevance
“…In our P-V-T data set, the St value ranges from −0.0020 to 35 ͒ and its pressure dependence for Au and Pt is unknown, we cannot directly estimate the deviatoric stress in the sample. For reference, Shim et al 36 reported the ͉St͉ value of CaSiO 3 perovskite at P = 18-96 GPa and T = 1238-2419 K ranged from −0.005 to 0.005. In addition, Dubrovinsky et al 37 reported that deviatoric stress in MgO is as small as 0.25 GPa at T = 850 K. Therefore, the stress state in the present EHDAC was expected to be minimal.…”
Section: A Experimental Resultsmentioning
confidence: 99%
“…In our P-V-T data set, the St value ranges from −0.0020 to 35 ͒ and its pressure dependence for Au and Pt is unknown, we cannot directly estimate the deviatoric stress in the sample. For reference, Shim et al 36 reported the ͉St͉ value of CaSiO 3 perovskite at P = 18-96 GPa and T = 1238-2419 K ranged from −0.005 to 0.005. In addition, Dubrovinsky et al 37 reported that deviatoric stress in MgO is as small as 0.25 GPa at T = 850 K. Therefore, the stress state in the present EHDAC was expected to be minimal.…”
Section: A Experimental Resultsmentioning
confidence: 99%
“…Since then, it had been considered to have a cubic crystal structure [e.g., Tamai and Yagi, 1989]. After theoretical studies predicted that a slightly distorted tetragonal structure is stable at static conditions [Stixrude et al, 1996], CaPv was experimentally confirmed to be tetragonal at room temperature [Shim et al 2000]. Recent experimental studies have shown that CaPv undergoes a phase transition from a tetragonal to cubic structure at 580 K at 50 GPa [Kurashina et al, 2004] and is cubic at LM P-T conditions [Komabayashi et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…This potentially indicates, that the calcite rhombohedral structure can be stable, in the natural environment, under pressure conditions of up to at least 14-24 GPa (Shim et al 2000). In our other studied samples, calcite was identified by analogy on the basis of its composition only; aragonite orthorhombic or trigonal structure of some of those grains may not be excluded.…”
Section: Depth Of Origin Of the Juina Diamond Hosted Carbonatites Anmentioning
confidence: 76%